Efficacy of Levetriacetam and Phenytoin as Combination Therapy in Infants Presented with Status Epilepticus - Samra Liaqat, Quratulain Khalid, Asad Mahmood Khan, Malik Abid Ali, Muhammad Faisal Javaid, Muhammad Salman Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Levetiracetam may be an effective and safer alternative to phenytoin as a second-line intravenous anticonvulsant for the treatment of juvenile convulsive status epilepticus. Objective of this study was to determine the efficacy of Levitriacetam and Phenytoin as combination therapy in infants presented with status epilepticus. Material and Methods: In this cross observational sectional study (01-02-2020 to 31-07-2020) at department of pediatrics mayo hospital Lahore. study the infants were enrolled of either gender and age less than 1 year that were suffering from a seizure with 5 minutes or more of continuous clinical seizure activity or recurrent seizure activity without recovery between seizures.Then these cases were started with both Phenytoin (Loading: 15 - 20 mg/kg IV *Maintenance: 5 - 8 mg/kg/d) and Levitriacetam (Loading dose5 10 mg/kg IV and Maintenance dose 10 – 30 mg/kg/dose q12 hours ) and were observed daily to look for fits. Efficacy was labelled as yes where there were no fits for 48 hours after the treatment. Results: In this study there were total 120 cases and out of these 74 (61.67%) were males and 46 (38.33%) females. Mean age of the subjects was 4.57±3.97 months. Mean duration of symptoms was 2.23±1.47 days. Out of 120, tonic clonic seizures were noted in 78 (65%) of the cases and 30 (25%) of the cases had family history of epilepsy. Efficacy was noted in 84 (70%) of the cases. Conclusion: Combination of Levetriacetam and Phenytoin is highly efficacious in infants presented with status epilepticus. Keywords; Levetriacetam, Phenytoin, Status epilepticus, Fits, Infantile seizures